Efficacy and Safety of Lercanidipine Combination in Hypertensive Patients - J Manolis, Athanasios; S Kallistratos, Manolis; Camafort, Miguel; Coca, Antonio (Journal of Hypertension and Cardiology, 2025)
Calcium channel blockers (CCBs) are widely used for the treatment of arterial hypertension, but they differ in terms of pharmacology, tolerability, and pleiotropic actions. Lercanidipine, a highly lipophilic third generation dihydropyridine, reduces blood pressure (BP) effectively as monotherapy and in combination without inferiority to other major antihypertensive classes. We systematically searched PubMed and the Cochrane Library (last update: September 1, 2025) and screened reference lists for additional studies. Evidence from dose finding trials, randomized controlled studies, large observational cohorts, and meta analyses shows clinically meaningful reductions in office, home, and ambulatory BP with lercanidipine, including in patients with diabetes, obesity, chronic kidney disease, or high cardiovascular (CV) risk. Fixed- dose combinations with renin angiotensin system blockers (e.g., enalapril) provide greater BP reductions than monotherapy and are associated with favorable neurometabolic profiles. Beyond BP control, lercanidipine improves central hemodynamics and arterial stiffness, favors endothelial biology, and contributes to left ventricular hypertrophy regression. Across comparative trials, lercanidipine is generally better tolerated than older dihydropyridines. Presents lower rates of vasodilatory adverse events, less sympathetic activation, while discontinuations due to adverse events are uncommon. Overall, lercanidipine particularly within single pill combinations offers effective, durable BP lowering across diverse patient profiles with a favorable safety and tolerability profile and pleiotropic benefits that extend beyond BP reduction. Figure 1. Graphical Abstract: Pleiotropic effects of Lercanidipine
Keywords: Lercanidipine; monotherapy; combination therapy; pleiotropic effects; adverse events